The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1021/bi000657x
|View full text |Cite
|
Sign up to set email alerts
|

Triplex Formation by Psoralen-Conjugated Chimeric Oligonucleoside Methylphosphonates

Abstract: Interactions between nuclease-resistant, 5'-psoralen-conjugated, chimeric methylphosphonate oligodeoxyribo- or oligo-2'-O-methylribo-triplex-forming oligomers (TFOs) and a purine tract found in the envelope gene of HIV proviral DNA (env-DNA) were investigated by gel mobility shift assays or by photo-cross-linking experiments. These chimeric TFOs contain mixtures of methylphosphonate and phosphodiester internucleotide bonds. A pyrimidine chimeric TFO composed of thymidine and 5-methyl-2'-deoxycytidine (C), d-PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 84 publications
3
9
0
Order By: Relevance
“…The EMSA data showed that the dissociation constant values of model triplexes fall in the range of low micromolar concentrations, under the conditions comparable to physiological ones. These K d values are in the range reported by other investigators for RNA and DNA triplexes 40 , 41 . Considering the specificity of LNA and 2-thioU modified TFOs, as well as hairpin interactions, we decided to test their potential in HeLa cells.…”
Section: Resultssupporting
confidence: 82%
“…The EMSA data showed that the dissociation constant values of model triplexes fall in the range of low micromolar concentrations, under the conditions comparable to physiological ones. These K d values are in the range reported by other investigators for RNA and DNA triplexes 40 , 41 . Considering the specificity of LNA and 2-thioU modified TFOs, as well as hairpin interactions, we decided to test their potential in HeLa cells.…”
Section: Resultssupporting
confidence: 82%
“…The propynyl group stacks with bases in duplexes and triplexes (29,30). Therefore, we designed propynyl-modified deoxythymidine (Pro) (Supplementary Figure S5a) and incorporated this residue into duplex- and G-quadruplex-forming oligonucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…The sequences and designations for each oligomer are shown in Tables 1 and 2. The psTFOs were synthesized on controlled pore glass (CPG) supports using an ABI model 392 DNA/ RNA synthesizer essentially as previously described (46). The protected nucleoside phosphoramidites and methylphosphonamidites were dissolved in anhydrous acetonitrile to a concentration of 0.15 M, and the nucleoside methylphosphonamidite solutions were stored for 2 h over 4 A°molecular sieves prior to use.…”
Section: Synthesis Of Oligonucleotidesmentioning
confidence: 99%